LEVERS OF CONTROL DAN KEUNGGULAN BERSAING: APAKAH PENGENDALIAN MANAJEMEN SEBUAH SISTEM? - Agnes Utari Widyaningdyah (Media Riset Akuntansi, Auditing & Informasi, 2020)
This study investigates the effect of Levers of Control (LoC) on competitive advantage with business environmental uncertainty as an antecedent variable. LoC as a form of company capability in facing environmental uncertainty is a source of company competitive advantage. Based on the resource-based theory, this research was conducted against the background of the decline in competitiveness of manufacturing companies in Indonesia during 2013-2018. The model of using LoC as a system outperforms the model of using LoC as a package to overcome business environmental uncertainty and to improve the companies’ competitive advantage. As a system, the LoC has interplay between the levers so that it can be of full use in realizing a competitive advantage.Levers of Control (LoC); Competitive Advantage; Business Environmental Uncertainty; Resource-based View